Academic self-efficacy and generic competences in education students of a national university in Lima - Muñoz Guevara, Liliana A. (2022)
The objective of the study was to determine the relationship between academic self-efficacy and generic competencies of education students at a national university in Lima. A sample of 178 participants was taken, a figure calculated from a total of 257 students, based on a confidence level of 95% confidence, an error of 5%, with a variability of 35.9. Under a quantitative approach, with a non-experimental, correlational design, the Academic Self-Efficacy Scale (ESSA) and the Questionnaire for the Evaluation of Generic Competencies were applied. The results indicated that the highest correlation corresponded between general self-efficacy and Leadership (rs = .511, p < .00; η2=.26). On the other hand, it should be noted that all correlations were significant, showing a positive relationship between both variables. It was concluded that there is a relationship between academic self-efficacy and generic competencies, i.e., students who consider themselves more effective when facing academic situations, manage to develop this type of competencies.